PENINGKATAN PERTUMBUHAN PADI VAR CIHERANG SETELAH DIINOKULASI DENGAN Azospirillum MUTAN MULTIFUNGSI PENAMBAT N2, PELARUT P DAN PENGHASIL FITOHORMON INDOLE ACETIC ACID (IAA). [The growth enhancement of rice var. Ciherang after inoculated with Azospirillum mutants multifunction capable of N2-fixation, P solubilization, and producing phytohormone indole acetic acid (IAA)] - Riyanti, Eny Ida; Listanto, Edy (Research Center for Biology-Indonesian Institute of Sciences, 2017)
Modern agriculture rellies on the application of fertilizer to enhanched plant growth. Excessive application of chemical fertilizers in the long term will decrease soil fertility, therefore the use of biological fertilizers is expected to reduce the negative impact. The aim of this study was to determine the effect of multi-functional Azospirillum for N2-fixation, phosphate solubilizerÃÂ and producing phytohormone Indole Acetic Acid (IAA) on the growth of rice plants Ciherang in the pot experiment conducted in the BB BiogenÃ¢â¬â¢s greenhouse. Two treatments were tested: types of inoculation (not inoculated, were inoculated with the wildtype AjB 6.4.1.2 and inoculated with mutant isolates AJM 3.7.1.14), and 4 levels of fertilizer application (not fertilized, a quarter dose of paddy fertilizer recommendations, a half dose of fertilizer rice in the rice fields, and the appropriate dose of fertilizer in paddy fields). Azospirillum used is wildtype isolate AjB 6.4.1.2 and mutant isolate AJM 3.7.1.14 isolated and and mutated in BB Biogen. Ciherang rice seed inoculated with Azospirillum on the cell density of 106 cells / ml at the different seedlings tub. After the age of 14 days after planting, the seedlings were transferred into pots with three plants per pot. Parameters measured were: plant height, number of tillers, number of panicles per clump, fresh weight and dry panicles per clump, weight of 100 grains, and the content of N and P stover. Results show that inoculantion, affect significantly on the number of panicles per hill, grain weight per panicle and the dry weight of grains per panicle.Â